The Role of Pesantren in Building Socio-Religious Independence of the Sasak Lombok Community during Colonialism - ., Murdianto (Journal of Ecohumanism, 2025)
This study examines the sociological role of pesantren (Islamic boarding schools) in fostering social resilience and resistance among the Sasak ethnic community of Lombok during the 19th-century colonial period. This research uses an ethnohistorical approach and critical discourse analysis to explore the interplay between Islamic education and community agency in confronting colonial dominance. Primary data were collected from colonial archives and local texts, and analyzed through the framework of everyday forms of resistance. The findings reveal that pesantren played a pivotal role as hubs of cultural resistance, strengthening the Sasak-Islamic identity and enabling alternative economic practices that challenged colonial systems. Additionally, pesantren contributed to social cohesion by serving as platforms for conflict resolution, implementing innovative agricultural methods, and ensuring food security for the community. This research underscores the transformative potential of Islamic educational institutions, positioning pesantren not only as centers of religious learning but also as agents of social change and cultural resilience. This study enriches the discourse on the sociology of Islamic education and postcolonial studies in Indonesia by highlighting the intersection of education, religion, and resistance.